ANALISIS POTENSI DANAU ANGGI GIJI DAN ANGGI GIDA SEBAGAI OBJEK WISATA ALAM KABUPATEN PEGUNUNGAN ARFAK PROVINSI PAPUA BARAT - Dowansiba, Erwin; Warami, Hugo; Martanto, Eko Agus (Universitas Papua, 2018)
This study aims to analyze the potential of Lake Anggi Giji and Lake Anggi Gida as natural attractions in the Arfak Mountains Regency of West Papua Province. The benefts of this study are (1) to encourage active participation of local communities in the development of natural attractions, (2) as a basis for the study of the application of policies and the role of institutions in the development of natural attractions, and (3) as a further research reference for the development of tourist attractions nature in the future. The tourism object itself is the embodiment of human creation, the system of life, the art of culture and history of the nation and the place of natural conditions that have the attraction to visit. The study was carried out in three (3) districts in the Lake Anggi Giji Region including Anggi District, Taige District and Sururey District, and 1 (one) Anggi Gida District for the Anggi Gida Lake Area in the Arfak Mountains District for approximately two months, namely July until with August 2017. Analysis of the data used in this study through the technique of scoring and classifcation. The method used in this study is a qualitative descriptive method Scoring and classifcation techniques are used to determine the classifcation of the potential level of tourist objects, namely: (1) Potential of tourism objects (Internal Potential) and (2) Potential of tourism areas (External Potential). Based on the results of a potential analysis of both the combined analysis of potential, internal potential and external potential of objects, the attractions of Lake Anggi Giji and Lake Anggi Gida have high potential to be developed with the following score scores: (a) internal potential has a score of 14 for both lakes, (b) external potential: a score of 21 for Lake Anggi Giji and a score of 20 for Lake Anggi Gida, and (c) a combined analysis score of 35 for Lake Anggi Giji and 34 for Lake Anggi Gida.